Average age of the medalists at major sporting events in judo - Lesko, L.; Segedi, I. (1st scientific and professional conference on judo "Applicable research in judo" - Book of abstracts, 2015)
The question of optimal age for best results in judo career, is frequently asked in the academic community and among sports coaches. The aim of this paper is to determine the period which represents the average age for winning Olympic games (OG) and World championship (WC) medals at the senior level in judo (total for both sexes and separately by gender). The specific aim of study is to determine a difference in the average age of the male and female medalists at major judo competitions. The same parameters will be considered on a sample of European judoka to determine the possible deviation from the overall global trend.